Argentine Youth : An Untapped Potential - World Bank (World Bank, 2012)
Argentina's youth, 6.7 million between the ages of 15 and 24, are an important, but to a certain extent untapped, resource for development. Over 2 million (31 percent) have already engaged in risky behaviors, and another 1 million (15 percent) are exposed to risk factors that are correlated with eventual risky behaviors. This totals 46 percent of youth at some form of risk. Today's youth cohort is the country's largest ever and it's largest for the foreseeable future. If policymakers do not invest in youth now, especially in youth at risk, they will miss a unique opportunity to equip the next generation with the abilities to become the drivers of growth, breaking the intergenerational spiral of poverty and inequality and moving Argentina back into the group of high-income countries. If youth are educated and skilled, they can be a tremendous asset for development. If not, they can burden society and public finances. Overall, Argentina is blessed with high enrollment rates in school, low levels of crime and violence, and moderate to low drug use by youth. However, youth employment, smoking and binge drinking (including its effect on traffic accidents), teen pregnancies, and HIV pose challenges for youth policy. While most youth in Argentina are educated, skilled, and healthy, a large group is potentially at risk of engaging in myopic behaviors, including school absenteeism and leaving, substance use and abuse, delinquency, crime, and risky sexual behavior. The consequences of these risky behaviors, unemployment, adolescent pregnancy, sexually-transmitted diseases, addiction, incarceration, violence, and social exclusion, make it difficult for youth to successfully transition to adulthood, imposing large costs on individuals and society. Applying the framework of the world development report 2007, this report examines the five life-changing transitions that all youth confront: leaving school and continuing to learn, starting to work, developing and maintaining a healthy lifestyle, forming a family, and exercising citizenship.